Strategi Pengembangan UMKM Melalui Legalitas Usaha dan Re-Branding Produk di Desa Kedungdalem Kabupaten Probolinggo - Dian Nova Kurniasari; Taufikurrahman T; Ida Syamsu Roidah (Yayasan Daarul Huda Kruengmane, 2023)
The development strategy for Micro, Small and Medium Enterprises (MSMEs) in Kedungdalem Village, Dringu District, Probolinggo Regency is carried out through assistance in business legality registration for MSME actors in Kedungdalem Village and product re-branding assistance for MSME partners in Kedungdalem Village. With the issuance of OSS (Online Single Submission), it makes it easy for MSME actors to obtain business legality in the form of NIB (Business Identification Number). In this digital era, it also makes it easy for MSME players to re-brand products in the form of logo making and packaging improvements. The obstacles faced by some MSME actors in Kedungdalem Village are the lack of understanding of the benefits of business legality ownership in the form of NIB, not having a business identity in the form of product logos and packaging displays that are still unattractive. The purpose of community service in Kedungdalem Village is expected to provide opportunities for MSME players in developing their businesses towards creative and innovative industries.The implementation of the method in the MSME development strategy in Kedungdalem Village is through several stages, including door to door socialization, Focus Group Discussion (FGD), assistance in making Business Identification Numbers (NIB), assistance in making logos and assistance in improving MSME partner packaging and creating social media accounts in the form of Instagram and special Websites for MSMEs in Kedungdalem Village. The results obtained from the MSME development strategy in Kedungdalem Village are an increase in knowledge from MSME actors regarding the importance of business licensing and product re-branding to create a positive image in the minds of the community.